Antioxidant supplementation during in vitro maturation - Amalia Ratna Kusumaningrum (Universitas Andalas, 2019)
During in vitro maturation (IVM), oocytes are exposed to different situations from in vivo which may cause oxidative stress. Supplementation of antioxidants to the culture media is effective in as antioxidant defences against reactive oxygen species (ROS). Antioxidant is safe, it has some side effects. This is reviewed in this paper. Studies reported, supplementation antioxidant with different dose showed different effects. Double-edged eﬀects of exogenous antioxidants on cellular responses during in vitro maturation depending potentially on their concentrations. Physiologic doses leading to beneficial eﬀects whereas high doses may result in harmful eﬀects.